The Change of a Changer: A Single Case Study of the Indigenization of a Chinese Counseling Psychologist - Wang, Dongmei; Wang, Baoyu (Frontiers in Psychology, 2021)
Over the past several decades, the increasing popularization of psychological counseling has underlined a strong need for an indigenous approach to counseling. The current study adopted a single-case study method to construct a narrative of the indigenization process of psychotherapy in mainland China based on a comprehensive description of one prominent counseling psychologist’s experience over the past half-century. Through interviews and records of fieldwork involving the psychologist (as the case) in 10 months between 2016 and 2017, the current study analyzed the indigenization process from the following three aspects: knowledge production, counseling practice, and student training. The findings showed that there was an underlying tension between the psychologist’s traditional wisdom and his professional training in scientific psychology during the indigenization process. However, the findings of this study further revealed something missing from previous studies. First, the client-centered counselor did not assume “power” during counseling sessions, which differs from critical viewpoints in medical anthropology. Second, the students being trained underwent fundamental changes in values rather than learning a technique or resolving problems. Third, the psychologist’s life history affected his thoughts and professional practice, which occurred in a sociocultural historical context. Finally, the implications for the future direction of the indigenization of counseling practice are discussed.